Chromosome-Scale Genome and Comparative Transcriptomic Analysis Reveal Transcriptional Regulators of β-Carotene Biosynthesis in Mango - Ma, Xiaowei; Luo, Xiang; Wei, Yongzan; Bai, Tuanhui; Shi, Jiangli; Zheng, Bing; Xu, Wentian; Li, Li; Wang, Songbiao; Zhang, Jisen; Wu, Hongxia (Frontiers in Plant Science, 2021)
Mango (2n = 2x = 40) is an important tropical/subtropical evergreen fruit tree grown worldwide and yields nutritionally rich and high value fruits. Here, a high-quality mango genome (396 Mb, contig N50 = 1.03 Mb) was assembled using the cultivar ‘Irwin’ from Florida, USA. A total of 97.19% of the sequences were anchored to 20 chromosomes, including 36,756 protein-coding genes. We compared the β-carotene content, in two different cultivars (‘Irwin’ and ‘Baixiangya’) and growth periods. The variation in β-carotene content mainly affected fruit flesh color. Additionally, transcriptome analysis identified genes related to β-carotene biosynthesis. MiPSY1 was proved to be a key gene regulating β-carotene biosynthesis. Weighted gene co-expression network analysis, dual luciferase and yeast one-hybrid assays confirmed that transcription factors MibZIP66 and MibHLH45 activate MiPSY1 transcription by directly binding to the CACGTG motif of the MiPSY1 promoter. However, the two transcription factors showed no significant synergistic effect on promoter activity. The results of the current study provides a genomic platform for studying the molecular basis of the flesh color of mango fruit.